Determinants of Hypertension in Outpatients in East Java, Indonesia - Makhfudli,; Susanto, Joko; Sairozi, Ali; Ubudiyah, Masunatul (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the prevalence of hypertension and to identify the causative factors. Method: The cross- cross-sectional study was conducted at Dr Soegiri Hospital, Lamongan, Indonesia, from March to July 2019, and comprised outpatients of either gender. Data was collected using a modified World Health Organisation STEPwise approach to surveillance questionnaire to identify the risk factors for hypertension. Data were analysed using the SPSS 16.0 statistical tool and logistic regression test. Results: Of the 184 subjects, 118(64.1%) were females and 66(35.9%) were males, and 96(52%) were aged <60 years. Overall, 120(65.2%) subjects were hypertensive; 80(66.7%) females and 40(33.3%) males. The two main factors that significantly influenced the incidence of hypertension were body mass index (p=0.001) and consumption of vegetables (p=0.013). After adjusting for confounding factors, only body mass index was found to affect the incidence of hypertension (odds ratio: 5.61; 95% confidence interval: 1.686-18.659). Conclusion: Body mass index and and dietary patterns affected the incidence of hypertension. After adjusting for confounding factors, only the former was found to have significant association with hypertension. Keywords: Blood pressure, Body mass, Hypertension, Feeding, Dietary.